"You can’t sell a marae": campus innovation at Massey University - Whiting, Gary; Whiting, Tyson (Architectural History Aotearoa, 2022)
Te Kupenga o te Mātauranga marae is located on the former Massey University Hokowhitu Campus in Palmerston North and has the distinction of being the first marae built on Crown land. A national hui on Māori Education was held at the Hokowhitu Campus (then Teachers College, not yet Massey University) in 1974 and it was here that Charlie Maitai challenged the then principal Pat Whitwell to build a wharenui on the new campus. That challenge was complete by the end of the 1970s. In 2015 the marae was sold by Massey University to a local developer as part of a wider real estate site package.